INNOVATIVE COMPONENT OF THE ECONOMIC GROWTH POTENTIAL OF LIVESTOCK PRODUCTION ENTERPRISES (Development Service Industry Management, 2025)
The article examines the essence, role, and features of enterprises' innovative potential in the agricultural sector, particularly the livestock industry. The scientific approaches of domestic researchers to determining the structure of an enterprise's economic and creative potential are analyzed, and its components are considered: resources, personnel, production, innovation, market, and management. It is substantiated that innovative potential determines an enterprise's ability to create new products, introduce modern technologies, and improve production processes, and that creative activity serves as a practical mechanism for realizing this potential. Particular attention is paid to the analysis of livestock farming development in Ukraine from 2019 to 2024. Based on statistical data, a stable, positive industry dynamic is established: an increase in production costs from 92.5 billion UAH in 2019 to 133.5 billion UAH in 2024. The leading role of dairy production, an increase in egg production, and a gradual expansion of the segment of other livestock products are determined. At the same time, the honey segment is characterized by relatively low growth rates. The article focuses on the main problems of the industry: financial difficulties for farmers, small and medium-sized businesses, the use of outdated technologies, low levels of innovation, and insufficient integration between producers and research institutions. It is substantiated that these factors hinder the development of livestock farming and reduce its competitiveness in world markets. The features of the innovative activities of enterprises engaged in livestock product production are summarized. The specifics of agricultural innovations are outlined, given the influence of natural and climatic conditions, regional differentiation, varying production cycle durations, and the high costs of implementing new technologies. It is determined that to increase the efficiency of innovative activity, comprehensive approaches are necessary that combine economic, technological, environmental, social, and political factors.It was concluded that the strategic direction for the development of livestock enterprises should be the active introduction of innovative technologies, greater integration with scientific institutions, support for innovative startups, and strengthening state support through subsidies and affordable lending. The implementation of these measures will contribute to the formation of a competitive and attractive investment in the agricultural sector, ensuring food security and sustainable development of livestock enterprises.
Keywords: innovation potential; agricultural sector; livestock products; agricultural innovations; economic growth